Cannabinoids, inflammation, and fibrosis. Issue 11 (19th July 2016) - Zurier, Robert B.; Burstein, Sumner H.
ABSTRACT: Cannabinoids apparently act on inflammation through mechanisms different fromthose of agents such as nonsteroidal anti‐inflammatory drugs (NSAIDs). As a class, the cannabinoids are generally free fromthe adverse effects associated with NSAIDs. Their clinical development thus provides a new approach to treatment of diseases characterized by acute and chronic inflammation and fibrosis. A concise survey of the anti‐inflammatory actions of the phytocannabinoids ∆ 9 ‐tetrahydrocannabinol (THC), cannabidiol, cannabichromene, and cannabinol is presented. Mention is also made of the noncannabinoid plant components and pyrolysis products, followed by a discussion of 3 synthetic preparations—Cesamet (nabilone; Meda Pharmaceuticals, Somerset, NJ, USA), Marinol (dronabinol;THC; AbbVie, Inc., North Chicago, IL, USA), and Sativex ( Cannabis extract; GW Pharmaceuticals, Cambridge United Kingdom)—that have anti‐inflammatory effects. A fourth synthetic cannabinoid, ajulemic acid (AJA; CT‐3; Resunab; Corbus Pharmaceuticals, Norwood, MA, USA), is discussed in greater detail because it represents the most recent advance in this area and is currently undergoing 3 phase 2 clinical trials by Corbus Pharmaceuticals. The endogenous cannabinoids, including the closely related lipoamino acids, are then discussed. The review concludes with a presentation of a possible mechanism for the anti‐inflammatory and antifibrotic actions of these substances. Thus, several cannabinoids may be considered candidates for development as anti‐inflammatory and antifibrotic agents. Of special interest is their possible use for treatment of chronic inflammation, a major unmet medical need.—Zurier, R. B., Burstein, S. H. Cannabinoids, inflammation, and fibrosis. FASEB J. 30, 3682–3689 (2016) www.fasebj.org